Implementation of Religious Moderation Values in College Students - Luluk Nur Hamidah; Syaefudin Achmad (al-Iltizam: Jurnal Pendidikan Agama Islam, 2022)
This Article aims to describe how the implementation of religious moderation values at Fakultas Tarbiyah dan Ilmu Keguruan UIN Salatiga. This article is one of the efforts to prevent the spread of radicalism among student who have been threatening. This research use a qualitative approach and type of field research. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using data presentation, data reduction, and drawing conclusions. The result of the study are a descpriotion of the religious moderation values at Fakultas Tarbiyah dan Ilmu Keguruan UIN Salatiga which include national commitment, tolerance, peace, and accommodation of lokal culture. National commitment is implemented with the culture of singing the “Indonesia Raya” at every event. Tolerance is implemented with mutual respect for each other. Peace is implemented with a culture of friendship and “tabayyun”. Lokal cultural accommodation is implemented with art performances.